Sirovena Bouček (Pteromalidae: Pireninae), a new member of the fig wasp community associated with Ficus microcarpa (Moraceae) - Li, Zi; Xiao, Hui; Huang, Da-Wei (Zootaxa, 2013)
Sirovena Bouček (Chalcidoidea: Pteromalidae, Pireninae) was known only from females of its type species, S. stigma Bouček, 1988. Males and host associations were both unknown. Both sexes of a second species of Sirovena, S. costallifera sp. nov., reared from Ficus microcarpa L. (Moraceae) in Yunnan, China, are described based on morphological characters and mitochondrial COI sequences. The males of S. costallifera show sexual dimorphism in body coloration, structure of the antennae and notauli, and body sculpture. Reliable host records of Pireninae are Cecidomyiidae (Diptera). Because midges also parasitize some figs, we speculate that S. costallifera is a parasitoid of some cecidomyiid midge that attacks fig syconia. A key to differentiate the two species is provided.